Health Coaching Strategies for Weight Loss: A Systematic Review and Meta-Analysis. Issue 4 (18th December 2020) - Sieczkowska, Sofia Mendes; de Lima, Alisson Padilha; Swinton, Paul Alan; Dolan, Eimear; Roschel, Hamilton; Gualano, Bruno
ABSTRACT: Health coaching has emerged as a potential supporting tool for health professionals to overcome behavioral barriers, but its efficacy in weight management remains unclear. We conducted a systematic review and meta-analysis to synthesize and evaluate the quality of evidence supporting the use of self-reported health coaching for weight loss. Seven electronic databases (PubMed, Web of Science, Scopus, Cochrane, Psyinfo, Virtual Health Library, and Scielo) were independently searched from inception to May 2020. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and quality of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation recommendations. Any study that investigated a self-reported health coaching intervention with the goal of inducing weight loss in individuals of any age, health, or training status was considered for inclusion. Quantitative data were analyzed using multilevel hierarchical metaregression models conducted within a Bayesian framework. A total of 653 studies were screened and 38 were selected for inclusion. The quality of evidence supporting outcomes based on the entire evidence base was very low and studies were deemed to have high risk of bias. Meta-analysis of controlled studies provided evidence of an effect favoring coaching compared with usual care but was trivial in magnitude [effect size (ES)0.5 : −0.09; 95% credible interval (CrI): −0.17, −0.02]. The multilevel extension of Egger's regression-intercept test indicated the existence of publication bias, whereas a sensitivity analysis based only on those studies deemed to be of high quality provided no evidence of an effect of coaching on weight loss (ES0.5 : −0.04; 95% CrI: −0.12, 0.09). Considered collectively, the results of this investigation indicate that the available evidence is not of sufficient quality to support the use of self-reported health coaching as a health care intervention for weight loss. This trial was registered at Prospective Register of Systematic Reviews (PROSPERO) as CRD42020159023.